Green growth opportunities for Asia - Sam Fankhauser; Alex Kazaglis; Sugandha Srivastav (Asian Development Bank (ADB), 2017)
This paper assesses the low-carbon economy in Asia: how large it is today and how well it will fare in the future. Using patent and trade data, it analyzes the potential of Asian economies to capture value from the design and export of low-carbon technologies, acknowledging that these are only two dimensions of a multidimensional low-carbon economy. It conducts country-level analysis to identify which technologies different countries can specialize in and potentially scale up. The work shows that, overall, Asia has an innovation specialization and revealed comparative advantage in climate change mitigation technologies. Particular strengths include efficient lighting, photovoltaics, and energy storage technologies. Further opportunities include nuclear and smart grids. However, within Asia, there are regional disparities, with countries such as the People's Republic of China, Japan, and the Republic of Korea outperforming others. This paper highlights how the analytical framework it presents can be used to strategically inform environmental policy makers and concludes with an overview of the green growth policy tool kit.
Keywords: Q42; Q43; Q54; Q56; 330; climate change; economic growth; energy; environment; urban development